Key Success in Fostering Human Development Index at the Local Level - Mujibur Rahman Khairul Muluk; Lestari Eko Wahyudi (Otoritas : Jurnal Ilmu Pemerintahan, 2022)
Human Development Index (HDI) determines human prosperity in different countries using value assets. In general, the primary measurement includes the three basic indices, namely education, health, and a decent standard of living. HDI is a measure of development and governance success in terms of economic growth and human development. Generally, studies on HDI take place at the national and regional levels, and comparisons of its achievements between countries, while those at the municipal level are limited. Studies on the determinants of the success of increasing HDI tend to focus on local governments' fiscal capacity and political will and rarely touch the capacity of public administration in managing government, specifically in the development planning stage. This study examined the increased success of the Malang City's HDI by adopting a logical framework (log-frame) analysis with secondary data from the Malang bureau of statistics. The results showed an 80.89 increase in HDI from 2014 to 2018, including the education and health indexes, with a decent standard of living. The increased success is shown by the Regional Medium Term Development Plan (RPJMD), including basic education development program, regional public hospital service programs, and food security program for education, health, and purchasing power indices. Therefore, the local government needs to maintain and enhance the HDI in both medium- and long-term plans. The novelty of this study lies in the use of a logical framework in preparing regional development plans that support efforts to increase HDI consistently in the medium term. This reinforces the need to strengthen the perspective of how to achieve development goals compared to other studies that focus more on the perspective of the substance of development.